Autonomous quantum Maxwell’s demon using superconducting devices - Martins, Gabriela Fernandes (2019)
During the last years, with the evolution of technology enabling the control of nano-mesoscopic systems, the possibility of experimentally implementing a Maxwell’s demon has aroused much interest. Its classical version has already been implemented, in photonic and electronic systems, and currently its quantum version is being broadly studied. In this context, the purpose of this work is the development of a protocol for the implementation of the quantum version of an autonomous Maxwell’s demon in a system of superconducting qubits. The system is composed of an Asymmetrical Single-Cooper-Pair Transistor, ASCPT, which has its extremities in contact with heat baths, such that the left one has a lower temperature than the right one. And of a device of two interacting Cooper-Pair Boxes, CPB’s, named as an ECPB, for Extended Cooper-Pair Box. The ECPB is also in contact with a heat bath and possess a genuine quantum feature, entanglement, being described by its antisymmetric and symmetric states, that couple capacitively to the ASCPT with different strengths. A specific operating regime was found where the spontaneous dynamics of the tunneling of Cooper pairs through the ASCPT, will led to a heat transport from the bath in contact with the left extremity of the ASCPT to the bath at the right. And so, as in Maxwell’s original thought experiment, the demon, which is composed by the ECPB and the island of the ASCPT, mediates a heat flux from a cold to a hot bath, without the expense of work. However as expected, the violation of the 2nd law of thermodynamics does not occur, as during the dynamics heat is also released to the bath in contact with the ECPB, compensating the decrease of entropy that occurs in the baths in contact with the ASCPT.